PAPERMAKING IN THE KOKAND KHANATE: STAGES OF HISTORICAL DEVELOPMENT AND SOCIAL SIGNIFICANCE - Begmatov Xurshid Isanaliyevich (Journals Park Publishing, 2025)
During the Kokand Khanate, the activities of papermaking workshops in Kokand and its surroundings underwent specific historical stages and rapidly developed socio-culturally. Also, the importance of paper in internal and external trade was high. The scientific opinions of research scientists on how paper was produced, the types of paper and its differences from Chinese and Samarkand papermaking are interpreted.
Keywords: Samarkand paper, Kokand paper, Mu'yi Mubarak, Chorku, Tul, Abri paper, sahhof (cover), musavvir (decorator), tablecloth (master of decorating texts in different lines), lavvah (master of decorating texts in different lines), lavvah (master of decorating the basis of the text), paper-cutter (master of cutting paper), abroz (master of abri papermaking)